PS02.059: ENHANCED EXPRESSION OF NT5E IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Kataoka, Atsuko; Yamada, Kazuhiko; Sugimoto, Takayuki; Hagiwara, Teruki; Nohara, Kyoko; Soma, Daisuke; Yamashita, Satoshi; Dohi, Taeko; Kawamura, Yuki I
Abstract: Background: Epigenetic changes such as DNA methylation are involved in the onset of ESCC. Previously, we have conducted transcriptome and methylome analyses using a paired specimen of ESCC and adjacent non-cancerous tissues and found promotor hypomethylation of NT5E with altered gene expression level in ESCC. NT5E has been known to be an extracellular nucleoside metabolism-related enzyme; however, the significance of its expression in ESCC has never been clarified. In this study, we aimed to evaluate the ESCC-related alteration of the expression of NT5E in using many cases of ESCC. Methods: Formalin-fixed, paraffin-embedded sections of surgical specimens from 67 ESCC patients who had undergone esophagectomy or endoscopic submucosal dissection between April 2008 and December 2015 in our hospital were immunostained using anti-NT5E antibody, and classified into NT5E-negative and NE5E-positive groups. To evaluate the mRNA expression of NT5E, qRT-PCR was performed using paired normal and ESCC frozen tissue samples from 24 patients. Results: Compared with matched normal mucosa, cancer tissues showed significantly higher NT5E mRNA expression ( P  < 0.05). Histologically, normal esophageal mucosa showed almost no staining of NT5E. Contrastingly, NT5E expression was clearly detected in 34 of 67 ESCC specimens (50.7%). There is no significant difference in clinicopathological factors between NT5E-positive and NT5E-negative groups. Conclusion: NT5E gene and protein expression was both upregulated in ESCC; its functional significance in relation to malignancy is underinvestigation. Disclosure: All authors have declared no conflicts of interest.